Novel Glycemic Index Based on Continuous Glucose Monitoring to Predict Poor Clinical Outcomes in Critically Ill Patients: A Pilot Study - Ha, Eun Yeong; Chung, Seung Min; Park, Il Rae; Lee, Yin Young; Choi, Eun Young; Moon, Jun Sung (Frontiers in Endocrinology, 2022)
Aim We explored the prospective relationship between continuous glucose monitoring (CGM) metrics and clinical outcomes in patients admitted to the intensive care unit (ICU). Materials and Methods We enrolled critically ill patients admitted to the medical ICU. Patients with an Acute Physiology and Chronic Health Evaluation (APACHE) score ≤9 or ICU stay ≤48 h were excluded. CGM was performed for five days, and standardized CGM metrics were analyzed. The duration of ICU stay and 28-day mortality rate were evaluated as outcomes. Results A total of 36 patients were included in this study (age [range], 49–88 years; men, 55.6%). The average APACHE score was 25.4 ± 8.3; 33 (91.7%) patients required ventilator support, and 16 (44.4%) patients had diabetes. The duration of ICU stay showed a positive correlation with the average blood glucose level, glucose management indicator (GMI), time above range, and GMI minus (-) glycated hemoglobin (HbA1c). Eight (22.2%) patients died within 28 days, and their average blood glucose levels, GMI, and GMI-HbA1c were significantly higher than those of survivors (p<0.05). After adjustments for age, sex, presence of diabetes, APACHE score, and dose of steroid administered, the GMI-HbA1c was associated with the risk of longer ICU stay (coefficient=2.34, 95% CI 0.54-4.14, p=0.017) and higher 28-day mortality rate (HR=2.42, 95% CI 1.01-5.76, p=0.046). Conclusion The acute glycemic gap, assessed as GMI-HbA1c, is an independent risk factor for longer ICU stay and 28-day mortality rate. In the ICU setting, CGM of critically ill patients might be beneficial, irrespective of the presence of diabetes.